Exploring the ocean environment GIS investigations for the earth sciences - Hall-Wallace, Michelle K.; Walker, C. Scott; Weeks, Jennifer A.; Kendall, Larry P. (Thomson/Cole, 2005)
Portions of the CD-ROM include ArcView GIS software of the Environmental Systems Research Institute (ESRI)